Rapists' Versus Non-Rapists' Attitudes Toward Women: A British Study - Harmon, G. A. (International journal of offender therapy and comparative criminology, 1995)
Three groups (incarcerated rapists, incarcerated non-rapists and nonincarcerated controls) were administered and completed Parry's (1983) Anglicized version of Spence, Helmreich and Stapp's (1973) Attitudes Towards Women Scale. Results of the seventy-one subjects showed that the incarcerated non-rapist group held the most traditional/conservative attitudes towards women. The present findings are discussed in terms of feminist viewpoint, current sociopolitical issues and cross-Atlantic research differences in relation to rape